Bargaining Mechanism in Islamic Economic System - Yudistia Teguh Ali Fikri (UIN Sunan Gunung Djati Bandung, 2018)
This article discusses the concept of bargaining position in the Islamic economic system. By using a literature study, this article finds a narrative that bargaining positions occur in goods or services. The conclusion are: bargaining must be carried out by more than one person. So, there are at least two people who transact (sellers and buyers). If there is only one person, the bargaining position certainly cannot happen. Examples of the many bargaining that occur are on the market. In a sale and purchase, those with higher bargaining rights are buyers. Whereas the seller will compensate the buyer for positive bargaining. Bidding is goods or services offered at a certain amount and price level and under certain conditions. There is also an offer in the Islamic economy that distinguishes it from conventional offers, that the goods or services offered must be transparent and specified in their specifications, how the condition of the goods, what are the advantages and disadvantages of the goods. The offer made does not harm the party submitting the request; and vice versa.